PREVALENCE OF IXODIDAE TICKS AND THEIR ASSOCIATION WITH DIFFERENT RISK FACTORS IN KHYBER PAKHTUNKHWA, PAKISTAN - M. Shoaib; I. Rashid; H. Akbar; A. A. Sheikh; S. H. Farooqi; M. A. Khan; S. Mahmood; F. A. Khan (Journal of Animal and Plant Sciences, 2022)
Ixodid ticks are in varying distribution patterns throughout Pakistan. They cause substantial losses to livestock industry in terms of hide loss and vector-borne disease transmission. This study was conducted in three districts of Khyber Pakhtunkhwa (KPK) from March 2018 to February 2019 with the aim of determining the prevalence and seasonal variation in tick species belonging to Ixodidae family in cattle population. A total of 1145 adult ticks were collected by a convenient method of sampling from 434 infested cattle of various breeds, age groups and sexes. Identification of ticks up to genus and species level was done with the help of specific morphological keys. The results showed higher prevalence of Rhipicephalus (Boophilus) microplus (77%) followed by R. (B) annulatus (70%), R. (B) decoloratus (54%), H. anatolicum (52%) and the least prevalence was recorded in R. (B) turanicus (12%). The prevalence of all ixodid tick species with exception of R. (B) annulatus and R. (B) decoloratus was significantly associated (p<0.05) with districts, breed, age and sex of cattle. Tick prevalence was higher in Achai and Friesian breeds, young stock and male animals. Prevalence of tick infestation was at its peak during summer and rainy seasons and remained low during winter season. In conclusions, that cattle tick R. (B) microplus was the dominant tick species infesting cattle population of KPK province and tick burden presented the highest record in summer season.
Keywords: Prevalence; Ixodid tick species; Cattle; Season; KPK.